Modeling of Train Sets in Tasks of Railway Stations Technical and Operational Evaluation - Kozachenko, D. M.; Klyga, O. V.; Kharchenko, Ye. V. (Science and Transport Progress, 2025)
Purpose. The purpose of the paper is to improve the methods of modeling train sets and shunting compositions that arrive for servicing at railway stations. Methodology. The task of train sets forming belongs to the tasks of railway transport studies. For its solution, operations research methods are used: statistical analysis to determine the number of cars in the design car flow; regression analysis to establish the relationship between the number of destinations, the length of the train set, and the number of cuts; linear integer programming for the distribution of cuts among the train sets; probability theory for the distribution of cars among the train sets. Findings. The execution of graphical and simulation modeling of station processes requires the formation of train sets design. The input data for performing the evaluation of the technical and technological parameters of stations, which are available without conducting special studies, are the number of cars arriving at specific destinations during the design period and the number of cars in the train sets and shunting compositions. Based on the provided input data, it is necessary to distribute the cars among the train sets in such a way that the structure of the consists corresponds to the operating conditions of the railway network. To solve this task, a methodology and algorithm for modeling the train sets and shunting compositions have been developed. The methodology for the formation of train sets includes the execution of six sequential stages: determining the number of cars for each specific destination in the design car flow arriving during the day; determining the number of train sets arriving from the incoming flow, and the number of cars in them; determining the average number of cuts in the designed train sets; establishing the number of cuts in the train sets; distributing the cars of the design car flow among the train sets; identifying cars with technical and commercial faults. Originality. The scientific novelty of the work lies in the fact that it improves the method of modeling design train sets used in the tasks of technical and operational evaluation of railway stations and sidings of industrial enterprises functioning. Practical value. The practical significance of the work lies in the fact that the proposed method allows process engineers and designers on the basis of a limited amount of input data, to form train sets for their further use in solving applied tasks of railway operation.